2010
DOI: 10.1007/s10616-010-9297-6
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance and expansion of hematopoietic stem/progenitor cells in biomimetic osteoblast niche

Abstract: In this study, we employed bio-derived bone scaffold and composited with the marrow mesenchymal stem cell induced into osteoblast to replicate a "biomimetic niche." The CD34(+) cells or mononuclear cells (MNC) from umbilical cord blood were cultured for 2-5 weeks in the biomimetic niche (3D system) was compared with conventional two dimensional cultures (2D system) without adding cytokine supplement. After 2 weeks in culture, the CD34(+) cells from umbilical cord blood in the 3D system increased 3.3-4.8 folds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 26 publications
2
33
0
2
Order By: Relevance
“…Several 3D models have been developed in order to mimic normal BM niches [171][172][173]. Artificial analogues of BM can accelerate the understanding of hematopoiesis in humans or can be suitable for ex vivo simulation of some aspects of human immune response.…”
Section: D Models For Expanding Normal Hsc a Tool For Clinical Therapymentioning
confidence: 99%
“…Several 3D models have been developed in order to mimic normal BM niches [171][172][173]. Artificial analogues of BM can accelerate the understanding of hematopoiesis in humans or can be suitable for ex vivo simulation of some aspects of human immune response.…”
Section: D Models For Expanding Normal Hsc a Tool For Clinical Therapymentioning
confidence: 99%
“…The CFU progenitors were more abundant in the 3D-system compared to the 2D-system (4.6-9.3 fold vs. 1.0-1.5 fold) after 2 weeks in culture, and the colony distribution in the3D-system showed a higher percentage of BFU-E and CFU-GEMM, whereas the 2D-system was mainly comprised of CFU-GM colonies. The LTC-ICs in the 3D-system showed 5.2-7.2 fold increase over 2 weeks and maintained the immature state of the hematopoietic progenitor cells (HPCs) over 5 weeks [112]. In an attempt to generate blood progenitor cells, agarose was modified with vascular endothelial growth factor.…”
Section: Cd38mentioning
confidence: 99%
“…Overall, these spheroid cultures formed submicroenvironments that were recognised differentially by HSCs, thus influencing their positioning near the hypoxic insides and inducing quiescence. Another study used a 3D hematopoietic progenitor cell culture system utilizing natural cancellous bone as a scaffold, seeded with osteoblasts and other bone marrow stromal cells [144]. In this system, certain parts of the ECM of the scaffold were still preserved, and the system demonstrated that it could maintain and expand haematopoietic progenitors efficiently.…”
Section: D Ecm Modelsmentioning
confidence: 99%